Factors Influencing Customer Attitudes towards Online Food Delivery Application after the COVID-19 Epidemic in Jordanian Restaurants - NAJDAWI, Bashar M. AL; KHASAWNEH, Mohammad; AL-MAKHADMAHj, Issam Mohammad; SHATNAWI, Hakam; KHALEEFAHj, Qusay; AL ROUSAN, Ramzi (Journal of Environmental Management and Tourism; Vol 14 No 2 (2023): JEMT, Volume XIV, Issue 2(66), Spring 2023, 2023)
Although several studies on technology trends and acceptance have been undertaken, few studies investigate the factors that influence customer attitudes toward food delivery apps depending on the Unified Theory of Acceptance and Use of Technology (UTAUT). The purpose of the study is to examine the use of Online Food Delivery (OFD) in Jordanian restaurants after the COVID-19 epidemic by applying UTAUT. In the northern and central regions of Jordan, 722 online questionnaires were gathered using Structural Equation Modeling (SEM). The results reveal that three factors significantly affect customers' decisions to use the OFD service: behavioral intention, pricing, and social influence. Furthermore, performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit positivity, trust, and perceived credibility significantly influence the behavioral intention to use. In addition, the moderating impacts of age, gender, and experience were examined using multigroup analysis. Some of the model's expected associations were shown to be moderated by the users' experience, but gender and age had no significant influence. The results have consequences for both research and practice implications.